Dynamics of electromagnetic waves generation by a rotating dielectric disk in a constant magnetic field—A revisit to Feynman’s “anti-flux” examples - Yurui Shang; Leo N. Y. Cao; Erming Su; Wei Tang; Zhong Lin Wang (AIP Advances)
Lenz’s law states that the change in magnetic flux over time induces an electromotive force around a circuit, commonly referred to as the flux rule. However, exceptions to the “flux rule” were discussed by Richard Feynman in The Feynman Lectures on Physics in 1963. The anti-flux phenomenon occurs when there is a large-size and rotating metal medium present in the circuit. This phenomenon has attracted the attention of many researchers, although most studies have predominantly focused on theoretical and mathematical calculations. Here, we have designed an experimental setup to investigate the generation of the electromagnetic waves by gear-driven rotating metal/semiconductor/dielectric disks with the presence of a static magnetic field. Low-frequency electromagnetic waves were surprisingly observed with frequencies up to 2 kHz for a disk rotating at 6.67 Hz (400 rpm) and energy levels reaching up to −70 dBm. Theoretically, such a result was not expected according to the classical Maxwell’s equations. Our interpretation is that the theory is based on Maxwell’s equations for a mechano-driven media system, which is to describe the electromagnetic behavior of a system that involves accelerated moving media/objects. This study proves that a moving medium is a source for generating electromagnetic waves.